2016
DOI: 10.1161/circulationaha.115.018531
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Proprotein Convertase Subtilisin/Kexin Type 9 (PCSK9) Predicts Future Risk of Cardiovascular Events Independently of Established Risk Factors

Abstract: PCSK9 is present in the circulation in 2 forms: a mature form composed of the PCSK9 prodomain attached to its catalytic domain and a form that is the result of furin cleavage at the Arg218-Gln219 peptide bond. 10,11 Commercially available and proprietary ELISA methods have been capable of measuring Background-The secreted protein proprotein convertase subtilisin/kexin type 9 (PCSK9) is a promising new target for lowering plasma low-density lipoprotein cholesterol and preventing cardiovascular disease (CVD). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
140
2
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(157 citation statements)
references
References 30 publications
10
140
2
5
Order By: Relevance
“…3,4 Recently, it has been discovered that proprotein convertase subtilisin/kexin type 9 has a major role in the regulation of LDL-C, and levels of soluble proprotein convertase subtilisin/kexin type 9 have been identified as a new marker of cardiovascular risk. 5 Although traditionally thought to reduce cardiovascular risk, the role of high-density lipoprotein cholesterol has now been brought into question by negative findings from clinical trials of drugs that increase high-density lipoprotein cholesterol and by negative Mendelian randomization studies. 3,4 In…”
Section: Lipid-related Risk Markersmentioning
confidence: 99%
“…3,4 Recently, it has been discovered that proprotein convertase subtilisin/kexin type 9 has a major role in the regulation of LDL-C, and levels of soluble proprotein convertase subtilisin/kexin type 9 have been identified as a new marker of cardiovascular risk. 5 Although traditionally thought to reduce cardiovascular risk, the role of high-density lipoprotein cholesterol has now been brought into question by negative findings from clinical trials of drugs that increase high-density lipoprotein cholesterol and by negative Mendelian randomization studies. 3,4 In…”
Section: Lipid-related Risk Markersmentioning
confidence: 99%
“…RR varied from 0.33 to 1.48 across the different studies but only one of the 7 studies showed a significantly positive association between PCSK9 and the risk of CVD events (RR, 1.48; 95% CI: 1.12-1.95; P<0.001). 24 Overall, circulating PCSK9 concentration as a continuous variable was not significantly associated with the risk of CVD events (RR, 1.12; 95% CI: 0.98-1.29, P=0.09). Significant heterogeneity across the studies was observed (I 2 =55.1%, Pheterogeneity=0.038).…”
Section: Data Extraction and Quality Assessmentmentioning
confidence: 82%
“…Further, fasting status and type of blood sample (serum or plasma) also differed across the studies, resulting in a large range of mean PCSK9 (94.3-546.5 ng/mL). 24,20 Differences in treatment regimen may have also contributed to the different results. Plasma PCSK9 predicted CVD events in CAD patients with medication alone but not in those with PCI/CABG treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Möglicherweise spielt hier die lebenslang niedrige LDL-Konzentration der Träger der PCSK9-"Loss-offunction"-Mutationen eine kausale Rolle. Hierfür spricht auch die Beobachtung, dass die Plamakonzentration von PCSK9 ein unabhängiger Prädiktor der KHK zu sein scheint [19]. [20,21].…”
Section: Entdeckung Von Pcsk9unclassified